Dilema Keseimbangan Kehidupan Kerja Guna Mewujudkan Profesionalitas Kerja Pada Dosen Tetap Wanita Pada Perguruan Tinggi di Indonesia - Kristin Juwita; Erminati Pancaningrum (STIE PGRI Dewantara Jombang, 2020)
This study aims to examine the effect of work-life balance on the performance of female lecturers through work-family conflict and family-work conflict as mediating variables. This research uses explanatory research. The population in this study were permanent lecturers throughout Indonesia. The sampling technique is done by purposive sampling. The analysis technique uses descriptive and structural equation modeling (SEM). The results of the analysis show that work-life balance can affect work-family conflict, family-work conflict, and the performance of female lecturers. However, work-family conflict does not affect the performance of female lecturers. Whereas family work conflict can affect the performance of female lecturers. Work-family conflict is not able to mediate the effect of work-life balance on the performance of female lecturers, but family work conflict can mediate work-life balance that affects the performance of female lecturers